Indikasi Budaya Hoabinh pada Alat Litik Temuan Singkapan di Situs Loyang Mendale - Ketut Wiradnyana (Balai Arkeologi Sumatera Utara, 2011)
AbstractTrought the lithic tool, the indication of cultural periodization and the development of culture could be refered to. Also, by the finding of a lithic tool in Loyang Mendale site. It can indicate time and cultural periodization which was growing at the time. Those understanding can be achieved by doing the description of the morphology and the technology on lithic equipment. In addition to the description, the comparison object can be done trought the lithic tool-making stages of processing compared with lithic tool around Loyang Mendale site that has a contemporary culture. Based on morphological and lithic technology in a tool of cultural sites hoabinh lowland and highland hoabinh culture sites produced relativaly similar morphology. In addition, the same technology as the technology during mesolithic culture that developed on the Loyang Mendale site has compatility with the hoabinh culture.